利用衛星測高與實測水文資料分析海表面與海面下地轉流 - 張繼鴻; Chang, Chi-Hung (2015)
許多研究已證實海洋環流對氣候穩定與人類生活極為重要性，其變化亦與潛在之天然災害高度相關，因此近幾世紀來，持續監測海洋環流一直是備受重視的議題。本研究使用多顆衛星測高資料、重力衛星測得之大地水準面模型(GOCE或GRACE)、實測水文資料求解全球中尺度地轉流流速。為了減少絕對動力水面高之誤差，本研究使用傳統pointwise法、spectral法與profile法對海水面高度與大地水準面模型進行處理，解算流速結果與TAO/TRITON、PIRATA提供之水深10 m處23站實測流速進行比較，結果顯示spectral法結果之平均均方根為10~15 cm/s，有70%~90%測站之均方根較傳統pointwise法小或有同等級精度(1 cm/s以內差值)；而使用profile法結果之平均均方根為8~10 cm/s，並有超過90%測站之均方根較傳統pointwise法小或是有同等精度，顯示profile法為三種方法中最佳。另外，GOCE大地水準面應用在時變地轉流計算上之，約有60%~80%之測站之均方根較GRACE小。而東西方向時變流速與實測資料之平均相關係數為0.6~0.7；南北方向則為0.3~0.4，使用不同方法與大地水準面對相關係數造成之影響並不明顯(平均差值0.1以內) 進一步分析地轉流流速、體積傳輸量與氣候指標之相關性，對特定洋流截面包含墨西哥灣流(Gulf Stream)、拉布拉多洋流(Labrador Current)與冬季北大西洋震盪指標(North Atlantic Oscillation, NAO)以及黑潮(Kuroshio Current)與多變異聖嬰現象與南方震盪指標(Multivariate ENSO Index, MEI)間之關係作探討，結果顯示東西向墨西哥灣流流速、體積傳輸量與冬季NAO之相關係數為0.7 (1年延遲)，或許與灣流路徑之南北移動有關；南北向之拉布拉多洋流流速，特別在深度500 m以下，相關係數0.5 (無延遲)，而通過截面之南北向總體積傳輸量亦呈現同樣結果，對於冬季NAO之快速反應推測與拉布拉多洋流之變化主要為正壓性質(barotropic)有關。在北太平洋，吾人選取黑潮通過巴士海峽、台灣東北方與黑潮擴張流處之截面，於巴士海峽近表層處之東西向、黑潮擴張流處之南北向流速和MEI存在最大負相關約 -0.4，體積傳輸量則為-0.3~ -0.4；而東西向黑潮擴張流流速和MEI則存在最大正相關約0.4，體積傳輸量則為0.3，相較於台灣東北邊截面之最大相關係數僅約0.1~0.2，於巴士海峽與黑潮擴張流處與MEI之相關性相對更加顯著。 Studies have shown that ocean circulations are highly important for the climate stability and human life. Their variations are also highly connected to potential natural hazards; therefore, continuous monitoring of ocean circulations has been a highly respected issue over the past centuries. The research uses multiple satellite altimetry data, satellite-only geoid model (GOCE or GRACE), in-situ hydrographical data to determine mesoscale geostrophic current velocities globally. To reduce the errors remain in ADT, the research adopts conventional pointwise approach, spectral approach, and profile approach to process Sea Surface Height (SSH) and geoid models. In-situ current meter observations at 23 stations fixed at 10m depth from TAO/TRITON and PIRATA were taken as ground truth. Results show that when adopting the spectral approach, around 70%~90% of stations gives Root Mean Square (RMS) smaller than or at same accuracy level (within 1 cm/s) compared with the pointwise approach and the averaged RMS is about 10~15 cm/s, while there are over 90% of stations giving RMS smaller than or at same accuracy level with pointwise approach and averaged RMS is around 8~10 cm/s when adopting profile approach, which better improves the conventional pointwise approach. GOCE geoid model was also proved to perform better than GRACE geoid in determining geostrophic currents from time-variant perspective with 60%~80% of stations giving smaller RMS. On the other hand, the average correlation coefficients are all around 0.6~0.7 and 0.3~0.4 in zonal and meridional direction, respectively, with no significant discrepancy when adopting different approach or geoid model (average difference within 0.1). The correlation coefficients between geostrophic current velocities, volume transports through the Gulf Stream (GS), Labrador Current (LC) and wintertime North Atlantic Oscillation (NAO) were estimated, while the correlations of Kuroshio Current (KC) and El Nio/Southern Oscillation (ENSO) were evaluated by using Multivariate ENSO Index (MEI). Results show the correlation coefficient of 0.7 with 1-year lag between GS and wintertime NAO in zonal direction which may relate to the north-southward shift of GS pathway, while LC velocities show the correlation coefficient of 0.5 in meridional direction with zero-lag. The meridional volume transport through the transect also shows the same maximum correlation coefficient and lag time. Such fast response may due to the barotropic nature of LC variability. In the North Pacific Ocean, transects through the Bashi Channel, the northeast of Taiwan, and Kuroshio Extension were chosen. Comparatively higher correlations with MEI are in the meridional currents through the Kuroshio Extension and near-surface zonal currents through the Bashi Channel with maximum negative correlation coefficient of -0.4 and -0.3~ -0.4 for volume transports; Zonal currents through Kuroshio Extension shows maximum positive correlation coefficient of 0.4 and 0.3 for volume transports. Results indicate that correlations in the transect through Bashi Channel and Kuroshio Extension are all higher than those in the transect of the northeast of Taiwan where only gives correlation coefficient of 0.1~0.2.